The legal regime of social networks and the challenges posed by access to these platforms - Sánchez Cano, María Jesús; Romero Matute, Yeray (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
Recently, we have seen how a Spanish political group represented in parliament annou-nced that it had filed legal action in the Spanish courts against Twitter, for an alleged violation of “fun-damental rights such as freedom of expression, the right to political participation, ideological freedom and the principle of political pluralism and equality, all of which are enshrined in the Constitution”. This news highlights several issues that are not usually considered by the common user when accessing any of the most popular social networks, such as Twitter, Facebook, Instagram or LinkedIn. Considering this situation, the nature of the contract will be analyzed from an international private law perspective, as well as the submission clauses included in the contract.
Keywords: social network; user; contract; submission clause